Digital Beamforming Architecture and Techniques for a Spaceborne Interferometric Ka-Band Mission - Younis, Marwan; Lopez-Dekker, Paco; Patyuchenko, Anton; Krieger, Gerhard (IEEE Radar Conference (RadarCon), 2013)
The paper presents the instrument concept and performance of a Ka-band single-pass interferemetric mission proposed for measuring topography and topographic changes. A formation flying constellation of two compact synthetic aperture radars (SAR) satellites equipped with innovative digital beamforming hardware and advanced operation modes is described.
DLR Import::2019-04-03